Penerapan Arsitektur Model View Controller dan Framework Zend dalam Pengembangan Aplikasi Category Online di PT XYZ - Raharjo, Bayu Ponco; David, Felix (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research discusses the implementation of the Model View Controller (MVC) architecture and Zend Framework in developing the Category Online application at PT XYZ, a leading retail company in Indonesia. The IT team at PT XYZ faced challenges in developing applications using PHP Native, and the adoption of the Zend Framework improved development efficiency. The application handles manual changes in item status across numerous branches, which is inefficient. The study focuses on developing the Transformation Class Product (TCP) module. The research method involves five stages, from requirements analysis to implementation, using a prototype model approach. System testing, utilizing black box testing during the User Acceptance Test (UAT) phase, was successful, indicating the effectiveness of the application's core functionalities. Thus, the implementation of MVC and Zend Framework in the Category Online application at PT XYZ has proven effective in enhancing the company's operational efficiency.